2009
DOI: 10.1128/iai.00155-09
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Neuraminidase Enhances Meningococcal Adhesion to Epithelial Cells through Interaction with Sialic Acid-Containing Meningococcal Capsules

Abstract: The underlying mechanisms of the epidemiological association between influenza virus infections and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 48 publications
0
46
0
Order By: Relevance
“…During the colder seasons, the nasopharyngeal temperature is likely even lower than 33°C, as observed by Keck et al at 25°C ambient temperature, possibly enhancing the effects on N. meningitidis adhesion phenotypes. In winter months, the rate of meningococcal disease cases rises quickly, and this has been linked to the pattern of seasonal flu (54). In light of our findings, it seems plausible that acquisition of N. meningitidis during winter, when ambient and nasopharyngeal temperatures are low and when N. meningitidis is therefore best equipped for host colonization based on its expressional profile, might be more efficient.…”
Section: Discussionmentioning
confidence: 80%
“…During the colder seasons, the nasopharyngeal temperature is likely even lower than 33°C, as observed by Keck et al at 25°C ambient temperature, possibly enhancing the effects on N. meningitidis adhesion phenotypes. In winter months, the rate of meningococcal disease cases rises quickly, and this has been linked to the pattern of seasonal flu (54). In light of our findings, it seems plausible that acquisition of N. meningitidis during winter, when ambient and nasopharyngeal temperatures are low and when N. meningitidis is therefore best equipped for host colonization based on its expressional profile, might be more efficient.…”
Section: Discussionmentioning
confidence: 80%
“…3, solid black bars) (P Ͻ 0.05). This increase was dependent on the viral NA sialidase activity, since it was not observed when the DF1 cells expressed the mutant MZ-NA-Y406F or MZdelNA-Y406F proteins with no detectable sialidase activity (54) (Fig. 3, solid black bars) or in the presence of 1 M of zanamivir (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies found no association between meningococcal disease and other respiratory viruses, such as adenovirus, parainfluenza virus, respiratory syncytial virus, or rhinovirus [11,12], which suggests that a specific pathophysiological process would be in play for influenza virus-meningococcus interactions. In a study of epithelial cell cultures, RameixWelti et al [13] found that a direct interaction between the influenza A virus neuraminidase and the N. meningitidis capsule enhanced bacterial adhesion to respiratory epithelial cells. This effect may promote N. meningitidis dissemination via the bloodstream [14].…”
Section: Case Discussionmentioning
confidence: 98%